ANALISIS FAKTOR PENENTU MINAT BERKUNJUNG KEMBALI PADA DESTINASI WISATA TAMAN LIMO JATIWANGI BEKASI. - Pebryani Lestari; Abdul Yusuf (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2020)
Pebryani Lestari, 2020. Analysis of Determinants of Interest in Revisiting the Taman Limo Jatiwangi Tourism Destination in Bekasi. Essay. Faculty of Economics and Business, Singaperbangsa Karawang University. This research was conducted using descriptive methods, namely collecting, presenting, analyzing and testing factor analysis, as well as making and suggesting. Samples were collected using random sampling technique with a sample size of 385 respondents and processed using SPSS 20. The results of this study indicate that there are 5 new factors that are formed from 21 indicators which are the influence of the determinants of interest in returning to the tourist destination of Taman Limo Jatiwangi Bekasi, these five factors are named Factor 1 which is named the Visitor Perspective Factor consisting of the Self indicator Fullfilment, Financial Security, Leisure Time, Relaxation, Amenities and Variety. Factor 2 is named the Expectation and Desire Factor consisting of indicators of Prestige, Romance, Wish Fullfilment and Local Activities. Factor 3 is named as the Destination Factor consisting of indicators of Fun Vacation Trip, Escape, Play, Strengthening Family Bonds, Educational Opportunity and Knowledge Driven. Factor 4 is named Implication Factor consisting of indicators of Business Travel and Government Business Travel. Factor 5 is given the name Factor consisting of indicators for Visiting Friends / Relatives and Sightseeing. Keywords: Determinants, Revisit Intention